Anaesthesia induced neuroprotection. - Sanders,RD; Ma,D; Maze,M (Best Pract Res Clin Anaesthesiol, 2005)
Anaesthetic agents display remarkable neuroprotective potential; here, we describe the evidence supporting its use and highlight areas for future development of the field. In particular the application of isoflurane and/or xenon as inhalational neuroprotectants is advocated and evidence for the neuroprotection provided by barbiturates and suppression of cerebral metabolic rate is discussed.